Etawa Goat Business Development Strategy in Karanganyar Village Langsa City - Rizki Hidal Muwahhid; Rini Mastuti; Rozalina Rozalina (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Karanganyar Village is located in Langsa City and has prospects for Etawa goat farming (Capra aegagrus hircus). The demand for meat produced by Etawa goats (milk and meat) constantly increases. Efforts have been made to increase the livestock population, production, and productivity to meet market demand. Quantitative descriptive research was conducted to analyze the external and internal factors influencing the development of the Village-owned enterprises (BUMG) for Etawa goat farming in Karanganyar Village, Langsa Baro District, Langsa City, and to formulate a business development strategy. The research locations were purposefully chosen using the purposive method, and the respondents were selected using the purposive sampling method. The study included 5 respondents: livestock owners, managers, disease supervisors and controllers, expert lecturers, and consumers. Data was collected through a questionnaire, and the respondents were determined using purposive sampling. The data were analyzed using the EFE matrix, IFE matrix, and SWOT matrix to analyze the external factors (opportunities and threats) and internal factors (strengths and weaknesses). The results of this study indicate that to increase goat milk production. Several measures can be taken, such as increasing the goat population, increasing the number of male broodstock to accelerate breeding, using substitute feed such as tofu dregs as an additional main feed along with forage, and utilizing goat manure as organic fertilizer. Establishing strict operational standards (SOP) and supervision by relevant agencies is urgently needed to ensure the effective implementation of the policies and the success of the goat farming business in Karanganyar Village.